USE OF RE-STORYTELLING METHODS IN DEVELOPING CHILDREN'S CONNECTED SPEECH IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Prima Journal of Integrated Studies, 2026)
This article extensively and deeply studies the issues of effective use of retelling methods in the development of children's coherent speech in preschool educational organizations. The theoretical and basic concepts of the retelling methodology, related practical methods, psychological and pedagogical foundations of the formation of children's coherent speech, its role in the development of the culture of thinking, expressive skills and creative approaches of students, pedagogical experiences, innovative demonstration methods, ways to introduce techniques that give the best results are discussed. At the end of the article, a conclusion, important recommendations and modern literature sources are given.
Keywords: Retelling, coherent speech, preschool education, development of oral speech, pedagogical methodology, creative thinking, communicative skills.